2007
DOI: 10.1177/1534735407309257
|View full text |Cite
|
Sign up to set email alerts
|

Lesson From Comparison of CAM Use by Women With Female-Specific Cancers to Others: It's Time to Focus on Interaction Risks With CAM Therapies

Abstract: There has been no examination as to whether the prevalence of complementary and alternative medicine (CAM) use, as well as personal factors associated with CAM use and predictive of CAM use for women with female-specific cancers, is similar to those in other diagnostic groups. The purpose of this review is to compare CAM use and personal factors associated with and predictive of CAM use by women with female-specific cancers to samples of other diagnostic groups. If it is the case that CAM use is similar across… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
33
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 66 publications
3
33
0
1
Order By: Relevance
“…In terms of breast cancer, recent studies indicate that CAM use among women may be as high as 90%. 75 Because breast cancer is the most frequently diagnosed cancer in women 2 and because more women survive breast cancer than any other type of cancer, 76 it is important to identify CAM interventions that can maintain and even improve health-related QOL for this disease group. 77 Exploratory survival analysis indicated a nonstatistically significant 42% risk reduction in cancer-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of breast cancer, recent studies indicate that CAM use among women may be as high as 90%. 75 Because breast cancer is the most frequently diagnosed cancer in women 2 and because more women survive breast cancer than any other type of cancer, 76 it is important to identify CAM interventions that can maintain and even improve health-related QOL for this disease group. 77 Exploratory survival analysis indicated a nonstatistically significant 42% risk reduction in cancer-related mortality.…”
Section: Discussionmentioning
confidence: 99%
“…However, Malekzadeh et al 8 identified 7 herbal remedies with potential to interact with drugs used by a population of 233 breast cancer patients. Recently, Eschiti 9 concluded that future research should focus on CAM therapy and drug interactions in specific groups that carry a high risk of clinically significant interactions. This survey thus aims to identify the occurrence of herbchemotherapeutic drug combinations in a group of cancer patients in Norway and to explore possible clinical consequences of these combinations.…”
mentioning
confidence: 99%
“…Around 40 % of cancer patients in Germany use CAM during or after cancer treatment [7]. Since the 1970s, the percentages of cancer patients in western industrialized nations using CAM has continually risen, from 25 to 49 % [7][8][9][10]. In the USA, Australia and Europe between 38 and 60 % of all cancer patients use CAM during the course of disease for therapeutic support [1,11,12].…”
mentioning
confidence: 99%